A cognitive semantic approach to redeemer (G?’?L) in Deutero-Isaiah - S. Ashdown (Acta Theologica)
This study draws on cognitive semantics to explore the radial category nature of Redeemer (G?’?l) as depicted by Holy One of Israel in Deutero?Isaiah and the thematic commonalties of the passages involved. The earthly office of G?’?l exhibits a radial structure of four models that entail several senses of the concept the people of Israel associated with the office of redeemer, these are: 1) Pentateuchal Model; 2) Royal Model; 3) Marital Model; and 4) Avenger Model. Pertinent to the discussion is the way in which Isaiah extends the title by pairing Redeemer with the Holy One of Israel six times in chapters 41, 43, 47, 48, 49, and 54 suggesting G?’?l fulfills a sacred office associated with restoring the broken covenant relationship between Yahweh and Israel. A fifth structural component to the sacred office, the Holiness Model, is proposed which suggests a five model structure for the category of Redeemer.